Labor market power and the effects of fiscal policy - Christian Bredemeier; Babette Jansen; Roland Winkler (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
We propose a new fiscal transmission channel based on countercyclical monopsony power in the labor market. We develop a Two-Agent New Keynesian model incorporating a time-varying degree of monopsony power, with workers valuing various job aspects and firms having wage-setting power, inversely related to the elasticity of labor supply to individual firms. As government spending increases, labor supply to individual firms becomes more elastic, creating more competition, larger fiscal multipliers, and stronger distributional consequences. We examine this channel's interactions with other fiscal transmission channels. Finally, we confirm empirically the model's prediction of reduced employer market power following government spending expansions.
Keywords: E62; J42; E25; E32; 330; fiscal policy; labor-market monopsony; income inequality